PSI-12 Effect of a carbohydrase mixture on apparent and standardized ileal digestibility of amino acids in dry extruded-expelled soybean meal fed to growing pigs - Song, Jichen (J Anim Sci, 2019)
Heat treatment could effectively decrease the antinutritional factors in soybean during meal processing. One such progress is the combination of extrusion with expelling, which produces the dry extruded-expelled soybean meal (DESBM), and there is a great interest in exploring its utilization as a dietary ingredient for swine. Thus, eight ileal-cannulated barrows (initial BW = 30 ± 1.3 kg) were used to determine the ileal amino acid (AA) digestibility of DESBM fed to growing pigs with or without multi-carbohydrase (MC) supplementation. Pigs were randomly assigned to 1 of 4 treatments in a replicated 4 × 4 Latin square design to give eight observations per treatment. The experimental diets were formulated to contain one of the two batches of DESBM (DESBM-1 and DESBM-2) as the sole source of protein. All diets contained titanium dioxide (0.3%) as an indigestible marker to calculate nutrient digestibility. Each experimental period lasted for seven days, and ileal digesta samples were collected on d 6 and d 7. The standardized ileal digestibility (SID) of AA were calculated using published mean values to estimate ileal endogenous AA losses. Data were analyzed using the mixed model procedures of SAS, and the final model had treatment, batch, and the interaction between treatment and batch as the main effects. In general, the SID of AA in DESBM-1 and DESBM-2 were not different, such as Ile, Lys, Met, Thr, and Val, which averaged 88.97%, 89.77%, 89.08%, 84.38%, and 86.85% respectively. There were no effects of MC supplementation on AID and SID of AA digestibility in DESBM except for the AID of Trp (P < 0.05). Also, there were no interaction effects of MC supplementation and batch on AA digestibility in DESBM. In conclusion, enzyme supplementation did not improve the AID and SID of AA in DESBM fed to growing pigs.